Influence of Decoupled Charge Structure and Filler on the Blasting Effect - Yiping Zhang; Yi Luo; Sipeng Wan; Yingxiang Tian; Huanchao Ding; Xiaoxiao Zhang; Chengcheng Fang; Yuyao Zhang (Shock and Vibration)
This study compared models of specimens with different filler media and decoupled charge structures in terms of the blasting effect. The test system combined a high-speed camera and high-speed static strain test analyzer. A physical model of a concrete single-borehole decoupled charge structure was designed to study the geometric elements of the blasting funnel, flyrock launch velocity, peak strain values, and distribution of the gravel lumpiness. The experimental results showed that for the same decoupling coefficient, when expandable polystyrene foam (EPS) was used as the filling medium, the radius, depth, and volume of the blasting funnel of the model specimen were larger, the flyrock launch velocity was slower, the peak stress of the specimen was higher, and the distribution of gravel lumpiness was more even. The relationship between the experimental index and the decoupling coefficient follows the changing trend of first increasing and then decreasing or first decreasing and then increasing. With air and EPS as the filling media, the concrete model specimens could achieve optimal blasting effects at decoupling coefficients of 1.83 and 1.69, respectively. The results confirm the feasibility and practicability of using EPS as a filler and can provide guidance and an experimental basis for the selection of the decoupling coefficient and filling medium in blasting engineering.